Formation of the concept "development of organizational culture" - Victor Sazonov; Antonina Lebedeva (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
Now industry condition in Russia is characterized by a low level of competitiveness and labor productivity. This is the reason of absence of opportunity to take the leader position in the world market. The relevance of the research is caused by the necessity to increase of labor productivity in Russia through the management of development of organizational culture industrial enterprises. The aim of the research is to substantiate the topicality of increasing labor productivity in Russia; to denote the relation between increase of labor productivity and development of organizational culture; to compare well known definitions of the concept «development of organizational culture»; to classify the principal factors influencing the result of management of organizational culture development; to define the concept «development of organizational culture» from the point of view of effective management, for using the increasing labor productivity. Methods: the systems approach, principle of comparative analysis and analogy, the qualitative synthesis method. Conclusions. The authors have substantiated the relevance and the necessity of increasing labor productivity in Russia through the management of development of organizational culture and analyzed the content of definitions of the concept «development of organizational culture». As a result it was shown that well known definitions do not disclose the specific character and regularity of development from the view point of influence on increasing labor productivity. The authors proposed the classification of factors influencing the result of management of organizational culture development and singled out the most important ones. The paper introduces the author's definition of the «development of organizational culture» from the viewpoint of effective management; its feature consists in demonstration of the process regularity and its relation with the volume and the character of investment.